Investigasi Performa Variasi Sudut Impeller Blade Terhadap Gaya Dorong Waterjet Thruster - Pristiansyah, Pristiansyah; Suzen, Zaldy Sirwansyah; Oktavianto, Mario; Subhan, Muhammad; Hasdiansah, Hasdiansah (Politeknik Negeri Padang, 2025)
Variations in ship propulsion are needed to assist in the water transportation purposes that will be used. Waterjet becomes one of the efforts for variations of the ship propulsion system on the waterjet occurs because the action of the thrust force that occurs causes the ship to move at a certain speed and the reaction of the fluid. The use of 3D Printing is starting to be developed and researched whether it is feasible to use in water transportation. 3D Printing technology or known as Additive layer manufacturing and the famous technology is Fused Deposition Modeling this technique is used to print products using filaments as material, the printed product has ideal geometry if it has a precise size and perfect shape. The testing process carried out at the Bangka Belitung state manufacturing polytechnic obtained the highest thrust results 30˚ angle with the number of blades 5 has the highest value with a thrust of 206 N and the lowest 45˚ 5 blade with 135 N thrust, the difference in angle affects the thrust generated.